Muhammad Amin Abdullah's Thought on Multicultural Islamic Education - Azizah Hanum OK (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
In the Era of Disruption 4.0, education should have become one of the media in forming positive attitudes towards various realities. The attitude in question is an attitude of being willing to accept, acknowledge, and respect other people with their respective ethnicities, this is also stated in the slogan "Bhinneka Tunggal Ika". The cultivation of these attitudes and values is the main attraction in the multicultural education system. It is based on this matter that the researcher examines the thoughts of Amin Abdullah. Amin Abdullah's thoughts are very prominent starting from the idea of integration-interconnection, which later became the jargon of UIN Sunan Kalijaga to this day. Then his thoughts contributed significantly to the discourse in creating the concept of tolerant, democratic Islamic education and upholding the values of unity and justice. Writing articles using qualitative research with library methods. This is done in order to get the concepts of Amin Abdullah's thoughts on Multicultural Education. The data sources come from books and journals that are nationally and internationally accredited. Amin Abdullah's thoughts on Islamic education are religious education that breathes peace, has sensitivity to social reality, prioritizes social safety, and is based on the values of unity and justice as contained in the Qur'an and hadith so that students are able to accept, recognize and respect the differences of others.